Method for preparing proton conductor electrolyte sintered body based on multi-element metal oxide

By mixing multi-metal oxide additives with BaZr1-xYxO3-δ powder, followed by ball milling and low-temperature sintering, the high-temperature and high-time sintering problem of BaZr1-xYxO3-δ was solved, resulting in a high-density and high-conductivity proton conductor electrolyte sintered body, supporting the application of medium- and low-temperature solid oxide batteries.

CN120943629APending Publication Date: 2025-11-14SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511117698.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-03-28
Filing Date
2025-08-11
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

In the prior art, the sintering temperature of BaZr1-xYxO3-δ is high and the sintering time is long, which leads to significant grain boundary resistance that hinders proton migration and reduces the overall conductivity. Furthermore, existing sintering aids only partially improve the density and fail to solve the grain boundary resistance problem.

Method used

A composite precursor was prepared by mixing multi-metal oxide additives such as Ni, Co, Mg, Cu, and Zn with BaZr1-xYxO3-δ powder, followed by ball milling, drying, and calcination. The precursor was then sintered at a lower temperature to form a dense proton conductor electrolyte sintered body.

Benefits of technology

It significantly reduced the sintering temperature by 100-150℃, increased the relative density to 96%, and achieved an electrical conductivity of 1.4 mS cm-1 under a humid argon-hydrogen atmosphere, supporting the application of medium- and low-temperature solid oxide batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120943629A_ABST
    Figure CN120943629A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a proton conductor electrolyte sintered body based on multi-element metal oxides, and belongs to the technical field of solid oxide electrolytes.The method comprises the following preparation steps that barium carbonate, zirconium oxide and yttrium oxide serve as raw materials to be calcined, and proton conductor oxide powder is obtained; mixing the multi-element metal oxide auxiliary agent with the proton conductor oxide powder, and processing to obtain a composite precursor; and carrying out compression molding on the composite precursor to obtain a green body, and sintering the green body in a muffle furnace to obtain a compact proton conductor electrolyte sintered body. According to the method disclosed by the invention, the sintering temperature is reduced by 100-150 DEG C, the density of a sintered body is improved, the conductivity reaches 1.4 mS.cm <-1 > in a wet hydrogen atmosphere at 600 DEG C, and the method is suitable for efficient preparation of the medium-temperature solid oxide fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid oxide electrolyte technology, and in particular to a method for preparing sintered proton conductor electrolytes based on multi-metal oxides. Background Technology

[0002] Replacing the oxygen-ion-conducting electrolyte in solid oxide batteries with a proton conductor is a promising strategy for reducing their operating temperature. In humid, reducing atmospheres, due to the charge carrier H... + With low activation energy and high material mobility, proton-conducting ceramics possess rapid and unique proton conduction characteristics, enabling the battery to operate at medium temperatures (400-700℃). BaZr 1-x Y x O 3-δ BaZr is a perovskite-structured material with high proton conductivity and excellent chemical stability. However, its practical application still faces the following key bottlenecks: 1. BaZr 1-x Y x O 3-δ Grain boundary resistance significantly hinders proton migration, leading to a decrease in overall conductivity; 2. Preparation methods based on liquid-phase synthesis, such as combustion, sol-gel, and spray pyrolysis, are used to prepare BaZr. 1-x Y x O 3-δ The material's preparation process is complex and expensive; solid-phase synthesis of BaZr... 1-x Y x O 3-δ It requires a high sintering temperature (≥1600℃) and a long sintering time (≥24h). The high sintering temperature leads to Ba volatilization, followed by the precipitation of a second phase (such as Y2O3), which significantly reduces BaZr. 1-x Y x O 3-δ The proton conductivity of an electrolyte.

[0003] Currently, sintering aids are commonly used to improve BaZr content. 1-x Y x O 3-δ Improving sinterability is a common strategy to address the above problems, and various transition or alkali metal oxides have been used to enhance the sintering performance of proton-conducting electrolytes. Current research primarily employs single metal oxides as sintering aids. For example, Chinese patent CN201310098766.3 discloses a method for improving the sintering performance of proton-conducting solid oxide fuel cell electrolytes, which lowers the sintering temperature by impregnating with nickel nitrate. However, this only partially improves density and does not solve the grain boundary resistance problem.

[0004] In response to the aforementioned technical phenomena, how can we reduce BaZr? 1-x Y x O3-δ Finding the right sintering temperature while simultaneously improving density and maintaining high proton conductivity is a pressing technical challenge. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing sintered proton conductor electrolytes based on multi-metal oxides, aiming to solve the problems of high sintering temperature and long time in the preparation of barium zirconate matrix proton conductor electrolytes in solid-state methods, while maintaining the conductivity of the material.

[0006] The method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides provided by this invention adopts the following technical solution:

[0007] A method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides includes the following preparation steps:

[0008] S1. Weigh out barium carbonate, zirconium oxide and yttrium oxide respectively and mix them, then calcine them to obtain proton conductor oxide powder;

[0009] S2. Take the multi-metal oxide additive and mix it with the proton conductor oxide powder obtained in step S1, and then ball mill, dry and calcine it in sequence to obtain the composite precursor.

[0010] S3. The composite precursor obtained in step S2 is ball-milled and dried, then pressed into shape to obtain a green body. The green body is then placed in a muffle furnace for sintering to obtain a dense proton conductor electrolyte sintered body.

[0011] Preferably, the proton conductor oxide powder in step S1 is Y-doped barium zirconate-based, with the structural formula BaZr. 1- x Y x O3, where 0.1≤x≤0.25.

[0012] Preferably, the metal element in the multi-metal oxide additive in step S2 includes at least two of Ni, Co, Mg, Cu, and Zn.

[0013] Preferably, the preparation method of the multi-metal oxide auxiliary agent in step S2 includes:

[0014] At least two of the following components—NiO, CoO, MgO, CuO, and ZnO—are directly mixed to obtain a multi-metal oxide additive; or

[0015] Take at least two of Ni(NO3)2, Co(NO3)2, Mn(NO3)2, Cu(NO3)2, and Zn(NO3)2 as raw materials, add citric acid and ethylenediaminetetraacetic acid, stir and heat, and then calcine to obtain a multi-metal oxide additive, wherein the calcine temperature is 750-950℃.

[0016] Preferably, the amount of the multi-metal oxide additive added in step S2 is 0.5-2.5 wt%.

[0017] Preferably, in step S2, the ball milling speed is 400 r / min, the ball milling time is 1-4 h, the calcination temperature is 900-1200℃, and the calcination time is 2-5 h.

[0018] Preferably, the pressing pressure in step S3 is 3-6 MPa, the sintering temperature of the green body is 1300-1450℃, and the sintering time is 4-10 h.

[0019] Preferably, the ball milling solvent is anhydrous ethanol or isopropanol, and zirconia grinding beads are added during the ball milling process.

[0020] In summary, the present invention has the following beneficial technical effects:

[0021] The high-temperature proton conductor oxide BaZr obtained in this invention 1-x Y x The relative density of O3 reached 96%, and the sintering density was reduced by 100-150℃; BaZr prepared using the method of this application 0.8 Y 0.2 O3 exhibited sufficient conductivity of 1.4 mS cm⁻¹ under a moist argon-hydrogen atmosphere. 1 The proton-conducting electrolyte prepared with multi-metal oxide sintering aids has advantages at lower temperatures, such as 600℃, which is conducive to the application of solid oxide batteries at medium and low temperatures. Attached Figure Description

[0022] Figure 1 The XRD pattern is obtained by pre-calcining the proton conductor oxide powder of Example 1 of this application with Ni-Zn binary oxide at 1100°C.

[0023] Figure 2 The XRD pattern is obtained by pre-calcining the proton conductor oxide powder of Example 2 of this application with Ni-Co binary oxide at 1100°C.

[0024] Figure 3 This is a scanning electron microscope image of the sintered body of the proton conductor oxide powder of Example 2 of this application after being mixed with Ni-Co binary oxide.

[0025] Figure 4 This is the XRD pattern of the proton conductor oxide powder of Example 4 of this application after being mixed with Ni-Zn-Cu ternary oxide and pre-calcined at 1100°C.

[0026] Figure 5This is a scanning electron microscope image of the sintered body of the proton conductor oxide powder and the Ni-Cu-Zn ternary oxide mixture of Example 4 of this application.

[0027] Figure 6 It is the electrical conductivity of the proton conductor sintered body of Embodiment 4 of this application.

[0028] Figure 7 This is the XRD pattern of the sintered body of the proton conductor oxide powder of Example 5 of this application after being mixed with a multi-metal oxide composed of Ni, Co, Mg, Cu and Zn.

[0029] Figure 8 It is the electrical conductivity of the proton conductor sintered body of Embodiment 5 of this application.

[0030] Figure 9 This is a scanning electron microscope (SEM) image of the sintered body of the proton conductor oxide powder mixed with a multi-metal oxide composed of Ni, Co, Mg, Cu, and Zn, according to Example 6 of this application.

[0031] Figure 10 It is the electrical conductivity of the proton conductor sintered body of Embodiment 6 of this application.

[0032] Figure 11 This is a scanning electron microscope (SEM) image of the sintered body of the proton conductor oxide powder mixed with a multi-metal oxide composed of Ni, Co, Mg, Cu, and Zn, according to Example 7 of this application.

[0033] Figure 12 This is a curve showing the relationship between the density of the proton conductor sintered body and the amount of sintering aid added in Example 7 of this application.

[0034] Figure 13 The conductivity of the proton conductor sintered body of Embodiment 7 of this application is stable after operating at 600°C for 100 hours.

[0035] Figure 14 This is the XRD pattern of the proton conductor oxide powder of Comparative Example 1 of this application after pre-calcination at 1100℃.

[0036] Figure 15 This is a scanning electron microscope image of the proton conductor sintered body of Comparative Example 1 of this application.

[0037] Figure 16 This is a scanning electron microscope image of the proton conductor sintered body of Comparative Example 2 of this application.

[0038] Figure 17 This is a comparison diagram of the density of proton conductor sintered bodies assisted by mono-, ternary, and multi-component additives in this application. Detailed Implementation

[0039] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings.

[0040] Raw material source:

[0041] All oxides used in this application are commercially available oxides.

[0042] NiO: High Purity Chemical Research Institute, Inc.

[0043] CoO: damas-beta;

[0044] MgO: Chengdu Jinshan Chemical Reagent Co., Ltd.;

[0045] CuO: Fuchen (Tianjin) Chemical Reagent Co., Ltd.;

[0046] ZnO: Chengdu Kelong Chemical Reagent Factory.

[0047] Example 1

[0048] A method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides includes the following steps:

[0049] 1) Using barium carbonate, zirconium oxide, and yttrium oxide as raw materials, and weighing them separately according to a mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.8:0.1, zirconium oxide ball milling beads were added and the mixture was ball-milled in a planetary ball mill to obtain a pre-calcined powder. The pre-calcined powder was then heated to 1100℃ at a rate of 3℃ / min and calcined for 2 hours. After cooling in the furnace, a proton conductor oxide powder was obtained. The proton conductor oxide powder is Y-doped barium zirconate-based, with the structural formula BaZr. 1-x Y x O3, where 0.1 ≤ x ≤ 0.25;

[0050] 2) Add 2wt% of Ni and Zn oxide, i.e., a binary metal oxide additive obtained by mixing NiO and ZnO, to the proton conductor oxide powder obtained in step 1). Use anhydrous ethanol as a medium, add zirconium oxide ball milling beads, and ball mill the mixture in a planetary ball mill for 1 hour at a speed of 400 r / min. Then, calcine it at a temperature of 900-1200℃ for 2-5 hours to obtain the composite precursor.

[0051] 3) The composite precursor obtained in step 2) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1400℃ and sintered for 5 h. After cooling in the furnace, a proton conductor electrolyte sintered body is obtained.

[0052] Reference Figure 1 The relative density of the proton conductor electrolyte sintered body prepared in Example 1 was measured using the Archimedes method and was 97%.

[0053] The conductivity of the proton conductor electrolyte sintered body prepared in Example 1 under a moist argon-hydrogen atmosphere was measured using the van der Burg method. The conductivity at 300℃-700℃ was 1.1-3.8 mS / cm. -1 .

[0054] Example 2

[0055] A method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides includes the following steps:

[0056] 1) Using barium carbonate, zirconium oxide, and yttrium oxide as raw materials, and weighing them separately according to a mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.9:0.05, zirconium oxide ball milling beads were added and the mixture was ball-milled in a planetary ball mill to obtain a pre-calcined powder. The pre-calcined powder was heated to 1000℃ at a rate of 3℃ / min and calcined for 2 hours, followed by furnace cooling to obtain a proton conductor oxide powder. The proton conductor oxide powder is Y-doped barium zirconate-based, with the structural formula BaZr. 1-x Y x O3, where 0.1 ≤ x ≤ 0.25;

[0057] 2) Add 2wt% of Ni and Co oxides, i.e., a binary metal oxide additive obtained by mixing NiO and CoO, to the proton conductor oxide powder obtained in step 1). Add zirconium oxide ball milling beads to anhydrous ethanol as medium and ball mill in a planetary ball mill for 1 hour at a speed of 400 r / min. Then, calcine at a temperature of 900-1200℃ for 2-5 hours to obtain the composite precursor.

[0058] 3) The composite precursor obtained in step 2) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1400℃ and sintered for 5 h. After cooling in the furnace, a proton conductor electrolyte sintered body is obtained.

[0059] Reference Figure 2-3 The relative density of the proton conductor electrolyte sintered body prepared in Example 1 was measured using the Archimedes method and was found to be 93%.

[0060] The conductivity of the proton conductor electrolyte sintered body prepared in Example 1 under a moist argon-hydrogen atmosphere was measured using the van der Burg method. The conductivity at 300℃-700℃ was 0.1-1.8 mS / cm. -1 .

[0061] Example 3

[0062] A method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides includes the following steps:

[0063] 1) Using barium carbonate, zirconium oxide, and yttrium oxide as raw materials, and weighing them separately according to a mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.8:0.1, zirconium oxide ball milling beads were added and the mixture was ball-milled in a planetary ball mill to obtain a pre-calcined powder. The pre-calcined powder was heated to 1100℃ at a rate of 3℃ / min and calcined for 2 hours, followed by furnace cooling to obtain a proton conductor oxide powder. The proton conductor oxide powder is Y-doped barium zirconate-based, with the structural formula BaZr. 1-x Y x O3, where 0.1 ≤ x ≤ 0.25;

[0064] 2) Add 2wt% of an oxide composed of Ni, Cu and Zn to the proton conductor oxide powder obtained in step 1), i.e., a ternary metal oxide additive obtained by mixing NiO, CuO and ZnO. Use anhydrous ethanol as a medium, add zirconium oxide ball milling beads and ball mill in a planetary ball mill for 1 hour at a speed of 400 r / min. Then, calcine at a temperature of 900-1200℃ for 2-5 hours to obtain a composite precursor.

[0065] 3) The composite precursor obtained in step 2) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1350℃ and sintered for 5 h. After cooling in the furnace, a proton conductor electrolyte sintered body is obtained.

[0066] The relative density of the proton conductor electrolyte sintered body prepared in Example 3 was measured using the Archimedes method and was found to be 87.6%.

[0067] Example 4

[0068] A method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides includes the following steps:

[0069] 1) Using barium carbonate, zirconium oxide, and yttrium oxide as raw materials, and weighing them separately according to a mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.8:0.1, zirconium oxide ball milling beads were added and the mixture was ball-milled in a planetary ball mill to obtain a pre-calcined powder. The pre-calcined powder was heated to 1100℃ at a rate of 3℃ / min and calcined for 2 hours, followed by furnace cooling to obtain a proton conductor oxide powder. The proton conductor oxide powder is Y-doped barium zirconate-based, with the structural formula BaZr. 1-x Y x O3, where 0.1 ≤ x ≤ 0.25;

[0070] 2) Add 2wt% of an oxide composed of Ni, Cu and Zn to the proton conductor oxide powder obtained in step 1), i.e., a ternary metal oxide additive obtained by mixing NiO, CuO and ZnO. Use anhydrous ethanol as a medium, add zirconium oxide ball milling beads and ball mill in a planetary ball mill for 1 hour at a speed of 400 r / min. Then, calcine at a temperature of 900-1200℃ for 2-5 hours to obtain a composite precursor.

[0071] 3) The composite precursor obtained in step 2) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1400℃ and sintered for 5 h. After cooling in the furnace, a proton conductor electrolyte sintered body is obtained.

[0072] Reference Figure 4-6 The relative density of the proton conductor electrolyte sintered body prepared in Example 4 was measured using the Archimedes method and was 94%.

[0073] The conductivity of the proton conductor electrolyte sintered body prepared in Example 4 under a moist argon-hydrogen atmosphere was measured using the van der Burg method. The conductivity at 300℃-700℃ was 0.2-2.3 mS / cm. -1 .

[0074] Example 5

[0075] A method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides includes the following steps:

[0076] 1) Using barium carbonate, zirconium oxide, and yttrium oxide as raw materials, and weighing them separately according to a mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.8:0.1, zirconium oxide ball milling beads were added and the mixture was ball-milled in a planetary ball mill to obtain a pre-calcined powder. The pre-calcined powder was heated to 1100℃ at a rate of 5℃ / min and calcined for 2 hours, followed by furnace cooling to obtain a proton conductor oxide powder. The proton conductor oxide powder is Y-doped barium zirconate-based, with the structural formula BaZr. 1-x Y x O3, where 0.1 ≤ x ≤ 0.25;

[0077] 2) Add 2wt% of an oxide composed of Ni, Co, Mg, Cu and Zn to the proton conductor oxide powder obtained in step 1), namely, a pentagonal metal oxide additive obtained by mixing NiO, CoO, MgO, CuO and ZnO. Use anhydrous ethanol as a medium, add zirconium oxide ball milling beads and ball mill the mixture in a planetary ball mill for 2 hours at a speed of 400 r / min. Then, calcine it at a temperature of 900-1200℃ for 2-5 hours to obtain the composite precursor.

[0078] 3) The composite precursor obtained in step 2) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1400℃ and sintered for 5 h. After cooling in the furnace, a proton conductor electrolyte sintered body is obtained.

[0079] Reference Figure 7-8 The relative density of the proton conductor electrolyte sintered body prepared in Example 5 was measured using the Archimedes method and was found to be 96.9%.

[0080] The conductivity of the proton conductor electrolyte sintered body prepared in Example 4 under a moist argon-hydrogen atmosphere was measured using the van der Burg method. The conductivity at 300℃-700℃ was 0.2-2.2 mS / cm. -1 .

[0081] Example 6

[0082] A method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides includes the following steps:

[0083] 1) Using barium carbonate, zirconium oxide, and yttrium oxide as raw materials, and weighing them separately according to a mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.8:0.1, zirconium oxide ball milling beads were added and the mixture was ball-milled in a planetary ball mill to obtain a pre-calcined powder. The pre-calcined powder was heated to 1100℃ at a rate of 5℃ / min and calcined for 2 hours, followed by furnace cooling to obtain a proton conductor oxide powder. The proton conductor oxide powder is Y-doped barium zirconate-based, with the structural formula BaZr. 1-x Y x O3, where 0.1 ≤ x ≤ 0.25;

[0084] 2) Add 1.5wt% of an oxide composed of Ni, Co, Mg, Cu and Zn to the proton conductor oxide powder obtained in step 1), namely, a pentagonal metal oxide additive obtained by mixing NiO, CoO, MgO, CuO and ZnO. Use anhydrous ethanol as a medium, add zirconium oxide ball milling beads and ball mill the mixture in a planetary ball mill for 1 hour at a speed of 400 r / min. Then, calcine it at a temperature of 900-1200℃ for 2-5 hours to obtain a composite precursor.

[0085] 3) The composite precursor obtained in step 2) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1400℃ and sintered for 5 h. After cooling in the furnace, a proton conductor electrolyte sintered body is obtained.

[0086] Reference Figure 9-10 The relative density of the proton conductor electrolyte sintered body prepared in Example 4 was measured using the Archimedes method and was 91.8%.

[0087] The conductivity of the proton conductor electrolyte sintered body prepared in Example 4 under a moist argon-hydrogen atmosphere was measured using the van der Burg method. The conductivity at 300℃-700℃ was 0.1-1.9 mS / cm. -1 .

[0088] Example 7

[0089] A method for preparing proton conductor electrolyte sintered bodies based on multi-metal oxides includes the following steps:

[0090] 1) Using barium carbonate, zirconium oxide, and yttrium oxide as raw materials, and weighing them separately according to a mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.8:0.1, zirconium oxide ball milling beads were added and the mixture was ball-milled in a planetary ball mill to obtain a pre-calcined powder. The pre-calcined powder was heated to 1100℃ at a rate of 5℃ / min and calcined for 2 hours, followed by furnace cooling to obtain a proton conductor oxide powder. The proton conductor oxide powder is Y-doped barium zirconate-based, with the structural formula BaZr. 1-x Y x O3, where 0.1 ≤ x ≤ 0.25;

[0091] 2) Add 1.5wt% of an oxide composed of Ni, Co, Mg, Cu and Zn to the proton conductor oxide powder obtained in step 1), namely, a pentagonal metal oxide additive obtained by mixing NiO, CoO, MgO, CuO and ZnO. Use anhydrous ethanol as a medium, add zirconium oxide ball milling beads and ball mill the mixture in a planetary ball mill for 1 hour at a speed of 400 r / min. Then, calcine it at a temperature of 900-1200℃ for 2-5 hours to obtain a composite precursor.

[0092] 3) The composite precursor obtained in step 2) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1350℃ and sintered for 5 h. After cooling in the furnace, a proton conductor electrolyte sintered body is obtained.

[0093] Reference Figure 11-13 The relative density of the proton conductor electrolyte sintered body prepared in Example 7 was measured using the Archimedes method and was 91.8%.

[0094] The conductivity of the proton conductor electrolyte sintered body prepared in Example 7 under a moist argon-hydrogen atmosphere was measured using the van der Burg method. The conductivity at 300℃-700℃ was 0.1-1.7 mS / cm. -1 .

[0095] Comparative Example

[0096] Comparative Example 1

[0097] The method for preparing the proton conductor electrolyte sintered body differs from that in Example 7 in that the composite precursor in step 2) of Example 7 was not added, while the remaining steps are the same as in Example 7.

[0098] Reference Figure 14-15 The relative density of the proton conductor electrolyte sintered body prepared in Example 7 was measured using the Archimedes method and was found to be 57.3%.

[0099] Comparative Example 2

[0100] A method for preparing a sintered proton conductor electrolyte includes the following preparation steps:

[0101] 1) Using barium carbonate, zirconium oxide and yttrium oxide as raw materials, the above raw materials were weighed according to the mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.75:0.125. Using anhydrous ethanol as a medium, zirconium oxide ball milling beads were added and ball milled in a planetary ball mill to obtain pre-calcined powder. The pre-calcined powder was heated to 1100℃ at a rate of 5℃ / min and calcined for 2h. It was then cooled with the furnace to obtain proton conductor oxide powder.

[0102] 2) The proton conductor oxide powder obtained in step 1) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1400℃ for sintering for 5 h and cooled with the furnace to obtain the sintered proton conductor electrolyte.

[0103] Reference Figure 16 The relative density of the proton conductor electrolyte sintered body prepared in Example 7 was measured using the Archimedes method and was found to be 59.5%.

[0104] Comparative Example 3

[0105] A method for preparing a sintered proton conductor electrolyte includes the following preparation steps:

[0106] 1) Using barium carbonate, zirconium oxide and yttrium oxide as raw materials, the above raw materials are weighed according to the mass ratio of barium carbonate:zirconia:yttrium oxide = 1:0.8:0.1. Anhydrous ethanol is used as the medium, and zirconium oxide ball milling beads are added to the mixture and ball milling in a planetary ball mill to obtain pre-calcined powder. The pre-calcined powder is heated to 1100℃ at a rate of 5℃ / min and calcined for 2 hours. It is then cooled with the furnace to obtain proton conductor oxide powder.

[0107] 2) Add 2wt% of Ni oxide to the proton conductor oxide powder obtained in step 1), add zirconium oxide ball milling beads in anhydrous ethanol as medium, and ball mill in a planetary ball mill for 2 hours at a speed of 400 r / min. Then calcine at a temperature of 900-1200℃ for 2-5 hours to obtain the composite precursor.

[0108] 3) The composite precursor obtained in step 2) is loaded into a tablet press and pressed into a circular green body with a diameter of 15 mm under a pressure of 4 MPa. The green body is then placed in a muffle furnace at 1350℃ and sintered for 5 h. After cooling in the furnace, a proton conductor electrolyte sintered body is obtained.

[0109] Reference Figure 17 The relative density of the proton conductor electrolyte sintered body prepared in Example 7 was measured using the Archimedes method and was found to be 82.9%.

[0110] The above are all preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape and principle of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing sintered proton conductor electrolytes based on multi-metal oxides, characterized in that, The preparation steps include the following: S1. Weigh out barium carbonate, zirconium oxide and yttrium oxide respectively and mix them. After ball milling, calcine to obtain proton conductor oxide powder. S2. Take the multi-metal oxide additive and mix it with the proton conductor oxide powder obtained in step S1, and then ball mill, dry and calcine it in sequence to obtain the composite precursor. S3. The composite precursor obtained in step S2 is ball-milled and dried, then pressed into shape to obtain a green body. The green body is then placed in a muffle furnace for sintering to obtain a dense proton conductor electrolyte sintered body.

2. The method for preparing a proton conductor electrolyte sintered body based on a multi-metal oxide according to claim 1, characterized in that, The proton conductor oxide powder in step S1 is Y-doped barium zirconate-based, with the structural formula BaZr. 1-x Y x O3, where 0.1≤x≤0.

25.

3. The method for preparing a proton conductor electrolyte sintered body based on a multi-metal oxide according to claim 1, characterized in that, The metal elements in the multi-metal oxide additive in step S2 include at least two of Ni, Co, Mg, Cu, and Zn.

4. The method for preparing a proton conductor electrolyte sintered body based on a multi-metal oxide according to claim 3, characterized in that, The preparation method of the multi-metal oxide additive in step S2 includes: At least two of NiO, CoO, MgO, CuO, and ZnO are directly mixed to obtain a multi-metal oxide additive.

5. The method for preparing a proton conductor electrolyte sintered body based on a multi-metal oxide according to claim 1, characterized in that, The amount of multi-metal oxide additive added in step S2 is 0.5-2.5 wt%.

6. The method for preparing a proton conductor electrolyte sintered body based on a multi-metal oxide according to claim 1, characterized in that, In step S2, the ball milling speed is 400 r / min, the ball milling time is 1-4 h, the calcination temperature is 900-1200℃, and the calcination time is 2-5 h.

7. The method for preparing a proton conductor electrolyte sintered body based on a multi-metal oxide according to claim 1, characterized in that, In step S3, the pressing pressure is 3-6 MPa, the sintering temperature of the green body is 1300-1450℃, and the sintering time is 4-10 h.

8. The method for preparing a proton conductor electrolyte sintered body based on a multi-metal oxide according to claim 1, characterized in that, The ball milling solvent is anhydrous ethanol or isopropanol, and zirconia grinding beads are added during the ball milling process.

Citation Information

Patent Citations

  • Method for improving sintering performance of electrolyte of proton conductor solid oxide fuel cell (SOFC)

    CN103165930A